Pengaruh Pendidikan dan Pelatihan (DIKLAT) Dan Kompetensi Terhadap Prestasi Kerja - Iftakhullah Ghufron Jaeni; Suparno Suparno; Nadya Fadillah F (CV. Ulil Albab Corp, 2024)
The purpose of this research is to determine the positive and significant Influence of Education and Training (DIKLAT) and Competency on the Work Performance of Bank ABC Syariah Head Office Employees. The data collection method used in this study was a survey conducted by distributing questionnaires created through Google Form. The research sample consisted of 265 respondents employees who are still actively working at Bank ABC Syariah and have attended DIKLAT or training organized by ABC. The data analysis used to process and analyze the research results was Structural Equation Modeling (SEM), utilizing SPSS version 25 and AMOS version 24 software.